Agarwood branch ethanolic extract: optimal extraction process conditions and cytotoxic effects - Abbas, Phirdaous; Hashim, Yumi Zuhanis Has-Yun; Mohd Salleh, Hamzah; Syed Abdul Azziz, Saripah Salbiah (IIUM Press, 2020)
Uninfected agarwood branch is readily available as raw material in agarwood plantation as new practices of agarwood plantation scheme were opted as substitute to the endangered wild type agarwood. The uninfected branch can be easily obtained during pruning process (one of plantation’s common maintenance procedure), throughout the years before inoculation stage. This current study aimed to investigate the optimal extraction process conditions of agarwood branch using ethanol as solvent system for maximal yield, and assess its cytotoxic effects towards MCF-7 breast cancer cells. Uninfected branch of Aquilaria subintegra was subjected to One Factor at a Time (OFAT) and Response Surface Methodology (RSM)-guided ethanolic extraction to achieve maximal yield. The extract was then subjected to cytotoxicity, cell attachment and cell viability assays, respectively. Optimization Run 2 (temperature 45 °C, solid-liquid ratio of 1:30, 16 hours maceration) gave the highest agarwood branch ethanolic extract (ABEE) yield of 44.70 ± 18.9 mg/g dried material (DM). Meanwhile Run 7 (temperature 45 °C, solid-liquid ratio of 1:10, 16 hours of maceration) gave the lowest yield (19.34 ± 14.1 mg/g DM). However, while maintaining the 16 hour-maceration, the model predicted a slightly lower yield of 30.232 ± 0.266 mg/g DM of ABEE with process conditions of 45 °C and solid-liquid ratio of 1:19 when the desirable parameters were factored in namely using (i) the most suitable temperature (that does not risk the bioactivities of the extract), and (ii) an economical volume of solvent. Crude ABEE obtained from the optimal process conditions resulted in cytotoxicity effects on MCF-7 breast cancer cells with IC50 estimate of 3.645 ± 0.099 µg/mL. The extract also affected MCF-7 cell attachment and viability with altered morphology. More work to elucidate the mechanism of actions of the extract are warranted; which could further lead to development of breast cancer natural product-based therapeutics.